Implementation of Fish and Plant Nutrition Technology On Aquaponic Systems - Khoiri, Rizky Dafa; Styawati, Styawati; Afredha, Arya (IC-ITECHS, 2024)
Catfish farming often faces challenges due to high stress levels in fish caused by instability in water pH and temperature, which disrupt metabolism, reduce appetite, and harm their health. This can lead to nutrient deficiencies for plants in aquaponic systems, causing ecological imbalances. Many farmers still rely on instinct to monitor pond conditions, making it difficult to detect changes in pH, temperature, and nutrient levels promptly, resulting in suboptimal water conditions and high fish mortality rates. To address this, a device equipped with sensors for real-time monitoring of pH, water temperature, and nutrient levels is necessary, helping farmers maintain ecological balance and reduce fish mortality. This research aims to ease catfish farming by integrating an automatic feeding system controlled by a servo and RTC and monitoring critical parameters like pH, temperature, and plant color through Thingspeak. Using the prototype method, the system was developed with ESP32, Arduino Microcontroller, pH sensor, DS18B20 temperature sensor, TCS3200 color sensor, buzzer, and servo. The aquaponics system design included scheduled nutrient supply for fish feed and an accurate feeding process activated at 12:00 PM, running the servo for 2 seconds with a buzzer alert. Testing confirmed the sensors’ ability to transmit data to Thingspeak and display it via LCD. However, the temperature sensor requires periodic calibration, as weather conditions significantly influence readings. During the rainy season, the lowest temperature recorded was 27.10°C, while the highest temperature during summer reached 29.32°C, demonstrating the system’s adaptability across seasons.